Kekerasan dalam Berpacaran (Studi Kasus: Lima Remaja Perempuan Korban Kekerasan dalam Berpacaran di DKI Jakarta) - Asniah, Ayu; Dalimoenthe, Ikhlasiah; Fitri, Meila Riskia (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2023)
This study aims to describe adolescent girls as victims of dating violence in DKI Jakarta and discuss the reasons why victims stay in violent relationships, the impact experienced by victims, and the analysis of patriarchal culture on adolescent girls who are victims of dating violence. This research uses a qualitative approach with a case study method. The data were obtained through observation, in-depth interviews, literature study, and documentation. The research subjects were five adolescent girls who experienced KDP, namely MA, CN, HO, YK, and DL. The findings of this study are that there are several reasons why adolescent girls (victims) survive dating violence. These reasons are influenced by two factors, namely internal and external factors. Then, the impacts experienced by these victims include psychological, physical, social life, and economic impacts. The reasons and impacts experienced by victims show that there are patriarchal cultural values that are rooted in dating, especially in dominant and manipulative former partners.